Effect of Different Types of Extractants in the Separation of Rare Earth Metals using Emulsion Liquid Membrane Method: A Review - Ninda Anisyabana; Anni Anggraeni; Uji Pratomo; Riska Anbar Fadiyah (Universitas Tadulako, 2021)
Rare Earth Metals (REMs) are minerals which needed in modern technology because it has unique chemical, catalytic, electrical and paramagnetic properties, so REMs have the potential to be applied in various fields. The similarity in the physical and chemical properties of REMs causes them to be difficult to separate from their parent minerals. Emulsion Liquid Membrane is an effective and efficient method for REMs purification and separation because in practice it only requires a small amount of solvent, the diffusion rate and mass transfer are high, fast, and simultaneous compared to the solvent extraction method which requires many extraction steps and requires a lot of solvents. In the emulsion liquid membrane method, one of the factors that can determine the success of the extraction process is the selectivity of the ligands/extractants. The extractants must be highly selective against the target REM ions, both in the external aqueous phase and the internal aqueous phase. Therefore, this review aimed to determine the selectivity of various types of extractants such as D2EHPA, Cyanex 302, Cyanex 572, (RO)2P(O)OPh-COOH, Aniline, and TBP on extraction efficiency and stripping efficiency in the separation of rare earth metals through the emulsion liquid membrane method.